BYHWD Alleviates Inflammatory Response by NIK-Mediated Repression of the Noncanonical NF-κB Pathway During ICH Recovery - Xiao, Wei; He, Zehui; Luo, Weikang; Feng, Dandan; Wang, Yang; Tang, Tao; Yang, Ali; Luo, Jiekun (Frontiers in Pharmacology, 2021)
Intracerebral hemorrhage (ICH) is a life-threatening type of stroke that lacks effective treatments. Inflammatory response following ICH is a vital response that affects brain repair and organism recovery. The nuclear factor κB (NF-κB) signaling pathway is considered one of the most important inflammatory response pathways and one of its response pathways, the non-canonical NF-κB signaling pathway, is known to be associated with persistent effect and chronic inflammation. NF κB-inducing kinase (NIK) via the non-canonical NF-κB signaling plays a key role in controlling inflammation. Here, we investigated potential effects of the traditional Chinese medicine formula Buyang Huanwu Decoction (BYHWD) on inflammatory response in a rat model of ICH recovery by inhibiting the NIK-mediated the non-canonical NF-κB signaling pathway. In the first part, rats were randomly divided into three groups: the Sham group, the ICH group, and the BYHWD group. ICH was induced in rats by injecting collagenase (type VII) into the right globus pallidus of rats' brain. For the BYHWD group, rats were administered BYHWD (4.36 g/kg) once a day by intragastric administration until they were sacrificed. Neurological function was evaluated in rats by a modified Neurological Severity Scores (mNSS), Corner turn test, and Foot-fault test. The cerebral edema showed the degree of inflammatory response by sacrificed brain water content. Western blot and real-time quantitative reverse transcription PCR tested the activity of inflammatory response and non-canonical NF-κB signaling. In the second part, siRNA treatment and assessment of inflammation level as well as alterations in the non-canonical NF-κB signaling were performed to determine whether the effect of BYHWD on inflammatory response was mediated by suppression of NIK via the non-canonical NF-κB signaling pathway. We show that BYHWD treated rats exhibited: (i) better health conditions and better neural functional recovery; (ii) decreased inflammatory cytokine and the edema; (iii) reduced expression of NIK, a key protein in unregulated the non-canonical NF-κB signaling pathways; (iv) when compared to pre-treated rats with NIK targeting (NIK siRNAs), showed the same effect of inhibiting the pathway and decreased inflammatory cytokine. BYHWD can attenuate the inflammatory response during ICH recovery in rats by inhibiting NIK-mediated non-canonical NF-κB signaling pathway.